A thermoresponsive poly(N-vinylcaprolactam-co-sulfobetaine methacrylate) zwitterionic hydrogel exhibiting switchable anti-biofouling and cytocompatibility1. Issue 18 (14th May 2015) - Yang, Boguang; Wang, Changyong; Zhang, Yabin; Ye, Lei; Qian, Yufeng; Shu, Yao; Wang, Jinmei; Li, Junjie; Yao, Fanglian
<x xml:space="preserve">Abstract</x> A new class of hydrogels were prepared from the combination of the non-ionic VCL with zwitterionic SBMA monomers, exhibiting anti-biofouling and cytocompatibility.